Heart Failure With Preserved Ejection Fraction: A Review of Cardiac and Noncardiac Pathophysiology - Gevaert, Andreas B.; Boen, Jente R. A.; Segers, Vincent F.; Van Craenenbroeck, Emeline M. (Frontiers in Physiology, 2019)
Heart failure with preserved ejection fraction (HFpEF) is one of the largest unmet clinical needs in 21st century cardiology. It is a complex disorder resulting from the influence of several comorbidities on the endothelium. A derangement in nitric oxide bioavailability leads to an intricate web of physiological abnormalities in the heart, blood vessels and other organs. In this review, we examine the contribution of cardiac and non-cardiac factors to the development of HFpEF. We zoom in on recent insights on the role of comorbidities and microRNAs in HFpEF. Finally, we address the potential of exercise training, which is currently the only available therapy to improve aerobic capacity and quality of life in HFpEF patients. Unravelling the underlying mechanisms responsible for this improvement could lead to new biomarkers and therapeutic targets for HFpEF.